Delivering Trauma-Informed Care in the Juvenile Justice Setting (Journal of Applied Juvenile Justice Services, 2021)
Youth taken from the home and placed in emergency shelter, secure detention, and residential settings are exposed to new sources of trauma and danger that may reactivate severe stress symptoms leading to re-traumatization. A juvenile justice center planned a trauma-informed, system-focused intervention that included recommended elements: appropriate assessments of trauma symptoms, evidence-based programs and treatments to build resilience skills in youth and families, staff training, community collaboration and partnerships, and a safe environment to reduce the risk of re-traumatization. The purpose of this study was to describe the implementation over two years of the trauma-informed, system-focused intervention in the juvenile justice center and associated effects on youth trauma symptoms. Current and past traumatic event exposure, change in youth participants’ emotional regulation, effects of an evidence-based, trauma-informed therapeutic intervention on youth participants’ stress symptoms, and quality of the organizational trauma-informed care plan were assessed. Although efforts to improve participant emotional regulation and post-traumatic stress symptoms did not demonstrate significant differences, efforts to screen for trauma exposure at intake provided important information about participant multiple traumas to assist with the therapeutic process. Efforts in changing organizational culture and policy did result in minor self-reported facility environmental improvements. For the practitioner, even when an intervention is well planned, results are not always positive in actual practice.